2021
DOI: 10.1080/03004279.2021.1955946
|View full text |Cite
|
Sign up to set email alerts
|

‘Wow! is that a birch leaf? In the picture it looked totally different’: a pragmatist perspective on deep learning in Norwegian ‘uteskole’

Abstract: This study investigates pupils' experiences with learning outside the classroom and discusses how these experiences might contribute to 'deep learning' according to a pragmatist theoretical framework and a situated perspective on knowledge. The data comprise materials from three months of fieldwork with participatory observations and qualitative interviews of pupils from two Norwegian primary schools. The results are interpreted according to John Dewey's two criteria for educative experiences, 'transaction' an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In addition, EOtC research has demonstrated positive effects on students' health, well-being, and academic achievement (Becker et al, 2019;Dettweiler et al, 2017;L. Mygind et al, 2019;Otte et al, 2019;Winje & Løndal, 2021b), including better biological stress regulation, brain function and development (Dettweiler et al, 2023) and improved attention spans and reduced disruptive behaviours among students with emotional, cognitive, and behavioural disabilities (Szczytko et al, 2018). EOtC has also been found to strengthen student-teacher relationships (E. Mygind et al, 2019), to have a positive effect on students' pro-social behaviour (Bølling, Niclasen et al, 2019) and social relationships (Bølling, Pfister et al, 2019), although the latter association is still inconclusive (Ellinger et al, 2023;Lauterbach, 2023).…”
Section: Education Outside the Classroom In The Nordic Countriesmentioning
confidence: 99%
“…In addition, EOtC research has demonstrated positive effects on students' health, well-being, and academic achievement (Becker et al, 2019;Dettweiler et al, 2017;L. Mygind et al, 2019;Otte et al, 2019;Winje & Løndal, 2021b), including better biological stress regulation, brain function and development (Dettweiler et al, 2023) and improved attention spans and reduced disruptive behaviours among students with emotional, cognitive, and behavioural disabilities (Szczytko et al, 2018). EOtC has also been found to strengthen student-teacher relationships (E. Mygind et al, 2019), to have a positive effect on students' pro-social behaviour (Bølling, Niclasen et al, 2019) and social relationships (Bølling, Pfister et al, 2019), although the latter association is still inconclusive (Ellinger et al, 2023;Lauterbach, 2023).…”
Section: Education Outside the Classroom In The Nordic Countriesmentioning
confidence: 99%